Understanding barriers of BIM-based knowledge management system: A case study of Indonesian state-owned construction enterprises - Utama Singgih Fitra; Negara Kartika Puspa; Wijatmiko Indradi (BIO Web of Conferences)
Construction companies experience obstacles to apply their knowledge in different cases due to the project’s complexity. This study highlights the barriers of knowledge management and BIM implementation in Indonesia construction industry. Identifying barriers to the knowledge management process and assessing the characteristics and advantages of BIM are potential areas for research. Data is collected by interviewing sources or informants from Indonesian State-Owned Construction Enterprises (BUMN) in Indonesia. Eight informants were selected with top management qualifications as BIM and knowledge management users. Nvivo was used to process and analyze qualitative data. The results show that the barriers of BIM-Knowledge management implementation in Indonesian State-Owned Construction Enterprises are (1) The condition of contract or standard of the owner, which has not fully adopted ISO BIM 19650 standards, (2) The lack of experts who are proficient in integrating KM-BIM, (3) the lack of Organizational Culture that support integration of KMBIM. This study assist in understanding the barriers to knowledge management when integrated with BIM. In addition, the study is expected to assist top management in providing strategies to reduce barriers to knowledge management through a better understanding of BIM-based knowledge management.